Excretion of triacylglycerol as a matrix lipid facilitating apoplastic accumulation of a lipophilic metabolite shikonin. (12th October 2022) - Tatsumi, Kanade; Ichino, Takuji; Isaka, Natsumi; Sugiyama, Akifumi; Moriyoshi, Eiko; Okazaki, Yozo; Higashi, Yasuhiro; Kajikawa, Masataka; Tsuji, Yoshinori; Fukuzawa, Hideya; Toyooka, Kiminori; Sato, Mayuko; et al.
Abstract: Plants produce a large variety of lipophilic metabolites, many of which are secreted by cells and accumulated in apoplasts. These compounds often play a role to protect plants from environmental stresses. However, little is known about how these lipophilic compounds are secreted into apoplastic spaces. In this study, we used shikonin-producing cultured cells of Lithospermum erythrorhizon as an experimental model system to analyze the secretion of lipophilic metabolites, taking advantage of its high production rate and the clear inducibility in culture. Shikonin derivatives are lipophilic red naphthoquinone compounds that accumulate exclusively in apoplastic spaces of these cells and also in the root epidermis of intact plants. Microscopic analysis showed that shikonin is accumulated in the form of numerous particles on the cell wall. Lipidomic analysis showed that L. erythrorhizon cultured cells secrete an appreciable portion of triacylglycerol (24–38% of total triacylglycerol), composed predominantly of saturated fatty acids. Moreover, in vitro reconstitution assay showed that triacylglycerol encapsulates shikonin derivatives with phospholipids to form lipid droplet-like structures. These findings suggest a novel role for triacylglycerol as a matrix lipid, a molecular component involved in the secretion of specialized lipophilic metabolites. Abstract : Plants produce various lipophilic metabolites, many of which are secreted from the cells. Triacylglycerol plays the role of a matrix lipid to facilitate the secretion of those lipid molecules.